A systematic Review: Hospital Admissions Linked to Drug Use - Salah Asmir Saleh Al-Harbi , Mubarak Astar Al-Dhafiri , Sultan Abdullah Sael Al-Harbi , Eid Muhammad Al-Jumaili , Waleed Ashawy Khlef Alshammari (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: This systematic review aims to synthesize recent literature on drug-related hospital admissions, providing insights into the incidence and preventability of these admissions, identifying common types of drug-related problems leading to hospitalization, and elucidating associated factors.Methods: A comprehensive search was conducted using PubMed and Google Scholar databases to identify studies examining hospitalizations due to drug-related problems. Additional articles were identified through manual searches of reference lists. Prospective and retrospective studies published in English between January 2018 and January 2023 were included.